Evaluation of photosynthetic performance and carbon isotope discrimination in perennial ryegrass (Lolium perenne L.) under allelochemicals stress - Hussain, M Iftikhar (Ecotoxicology (London, England), 2017)
Ferulic (FA) and p-hydroxybenzoic acid (pHBA) are commonly found as phenolic compounds (PHC) in many forage and cereal crops. Although the effects of these PHC on seedling growth are relatively explored, not many information is available regarding the phytotoxicity on ecophysiological processes of perennial ryegrass adult plants. The experiment was conducted with the aim to evaluate the phytotoxic potential of PHC on the seedling growth, leaf water relation, chlorophyll fluorescence attributes and carbon isotope discrimination adult plants of perennial ryegrass (Lolium perenne L.). The results clearly indicated that PHC behaved as potent inhibitors of chlorophyll fluorescence yield (Fv/Fm) in leaves of L. perenne and plants showed poor tolerance against allelochemicals stress. Quantum yield (ΦPSII), chlorophyll fluorescence quenching (qP) and non-photochemical quenching (NPQ) were decreased following exposure to FA and pHBA. The portion of absorbed photon energy that was thermally dissipated (D) in L. perenne was decreased. Exposure of the L. perenne seedlings to FA and pHBA stress led to a decrease in fresh/dry weight, relative water content and leaf osmotic potential. Carbon isotope composition ratio (δ13C) was significantly less negative than the control following treatment with FA or pHBA. The results suggested that PHC uptake was a key step for the effectiveness of these secondary metabolites and their phytotoxicity on L. perenne adult plants was mainly due to the alteration of leaf water status accompanied by photosystem II damage. Acquisition of such knowledge may ultimately provide a better understanding about the mode of action of the tested compounds